Barriers for Responding to Pediatric Out‐of‐Hospital Cardiac Arrest During Emergency Medical Calls: A Qualitative Study - Astrid Rolin Kragh; Sofie Have Kjærholm; Louise de Claville Holland Flarup; Anne Juul Grabmayr; Liv Borch‐Johnsen; Fredrik Folke; Tine Tjørnhøj‐Thomsen; Christian Hassager; Carolina Malta Hansen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Rapid recognition of pediatric out‐of‐hospital cardiac arrest (POHCA) is a critical component to prompt initiation of bystander interventions. We aimed to investigate barriers for responding to POHCA during emergency medical calls. Methods and Results We included all POHCA calls (aged 0–18 years) from the emergency dispatch center in the Capital Region of Denmark between 2018 and 2021 and excluded POHCAs with no resuscitation order, found dead, where trained health professionals were on site, or where there was no possibility for initiation of cardiopulmonary resuscitation. A qualitative analysis was undertaken. POHCA calls were divided according to the speed of telecommunicator‐recognition into 3 groups: POHCA recognition within 90 seconds (group 1), POHCAs recognition >90 seconds (group 2), and POHCAs recognized by the emergency medical services at ambulance arrival (group 3). A total of 20 calls were included. We identified 3 major barriers to telecommunicator recognition of POHCA. First, prolonged conversations between callers and telecommunicators focusing on the cause of the child's condition rather than adherence to the assessment of consciousness and breathing. Second, challenges in assessing breathing such as cases where the child had agonal or unregular breathing or gasping breaths. Finally, callers who were unable to communicate or follow instructions from the telecommunicator. Conclusions Telecommunicator recognition of POHCA is challenged by factors such as prolonged conversations focusing on causes rather than initiating bystander interventions, barriers in assessing breathing, as well as callers' abilities to partake in communication with telecommunicators. Efforts to address these barriers in current dispatch protocols may improve recognition of POHCA.